Support for political mobilization and protest in Egypt and Morocco: an online experimental study. Issue 2 (2nd September 2017) - Lemieux, Anthony F.; Kearns, Erin M.; Asal, Victor; Walsh, James Igoe
Abstract: Why do individuals engage in or support acts of contentious politics? Building from previous work, this article uses a 2 (high/low grievance) × 2 (high/low risk) × 2 (high/low opportunity) online experimental design to examine the impact of these factors on political action with participants from Egypt ( n  = 517) and Morocco ( n  = 462). Participants assumed a first-person perspective as a member of a fictional oppressed ethnic minority group in one of eight vignettes. Participants then indicated the extent to which they would engage in various forms of protest and violence, and how justified such actions were. Participants answered several social-personality measures: Social Dominance Orientation (SDO), Right Wing Authoritarianism (RWA), and Activism and Radicalism Intentions Scale (AIS and RIS). Analyses show that higher SDO and RIS scores largely drive violent engagement and justification for these actions. Higher AIS scores predicted protest engagement and justification, while SDO negatively influenced non-violence. RWA scores decreased engagement in and support for any form of political action. In contrast with previous experimental findings, grievance did not impact decisions about political mobilization.